Clinical evaluation of patients patch tested with plant series: A prospective study - Suraj V Davis; S D Shenoi; S Prabhu; A Shirwaiker; C Balachandran (Wolters Kluwer Medknow Publications, 2011)
Background: Plants are ubiquitous in nature and are essential for human life, though some do have detrimental effects. In India, there are various indigenous and foreign plants that are well known to cause dermatitis, Parthenium hysterophorus being the foremost. Aims of the Study: To study the clinical features of patients presenting with plant dermatitis and evaluate plant allergen series patch test results. Materials and Methods: 50 patients with suspected plant dermatitis were evaluated regarding evolution of dermatitis, precipitating factors and contact with various plants. 31 patients (62%) complained of photo sensitivity and 24 (48%) had involvement of sun-exposed areas. Our provisional diagnoses included allergic contact dermatitis in 16, air borne contact dermatitis in 9, phytophotodermatitis in 7, photodermatitis in 6, airborne contact dermatitis to other causes in 4, phytodermatitis in 3. Patients were patch tested with Indian standard series of allergens as well as plant allergen series consisting of common allergenic plants of local flora in and around Manipal and also with plants strongly suspected by the patient. 35 tested positive with maximum positives (26 patients, i.e., 52%) to Parthenium hysterophorus (Compositae). Results: The result of patch testing was correlated with the history and clinical examination and relevance established. Conclusions: Majority of the patients with clinically suspected plant dermatitis belonged to 3 rd or 4 th decade and Parthenium was the leading plant allergen Sensitization to Leguminosae plants and Hopea ponga, seen in 9 cases, have not been reported earlier in literature.